KOMPENSASI DAN LINGKUNGAN KERJA PERAN MEDIASI MOTIVASI DALAM MENINGKATKAN KINERJA KARYAWAN PT AGUNG TOYOTA CABANG DURI - Handoyo, Leonardus Teguh; Arfi, Lingga Ramadhana; Suryatunnisak, Suryatunnisak (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
Compensation and Work Environment The Mediating Role of Motivation in Improving Employee Performance at PT Agung Toyota Duri Branch. The population in this study was the total number of employees of PT Agung Toyota Duri Branch, totaling 86 people. Meanwhile, in sampling this research used a saturated sampling technique, that is, the entire population was sampled because the population was relatively small, namely 86 people.This research uses primary data, namely data obtained from questionnaire results as an instrument to prove the research results. Meanwhile, secondary data used includes data regarding the number of employees, organizational structure and general description of the company. To test the hypothesis in this research, we use a structural equation model with the help of the SmartPLS program. The research results show that 1) compensation has a positive and significant effect on motivation, 2) the work environment has a positive and significant effect on motivation, 3) compensation has a positive and significant effect on performance, 4) the work environment has a positive and significant effect on performance, 5) motivation has a positive effect and significant to performance, 6) compensation influences performance through motivation, and 7) the work environment influences performance through motivation. Keywords : Compensation, Work Environment, Motivation and Performance